Fibrinolysis in the Pigeon (Columba livia) - Ahmad, Nasreen; Dube, B; Agarwal, G P; Dube, Ramakanta (Thrombosis and Haemostasis, 1979)
The presence of plasminogen activator in the euglobulin fraction of pigeon plasma, was demonstrated by conspicuous lysis on unheated fibrin plates; human as well as bovine fibrin were susceptible to lysis. The presence of free plasmin in euglobulin fraction was indicated by lysis on heated fibrin plates.